Mechanics to improve writing skills among students of tenth year “a” basic general education, afternoon session, at escuela de educación básica "Miguel Riofrío”, in Loja city during the 2020 - 2021 school year. - Abrigo Guarnizo, Franco Guillermo (2021)
The objective of this research work was to improve writing skills through the application of mechanics among students of tenth year “A” Basic General Education, afternoon session, at Escuela de Educación Básica "Miguel Riofrío”, in Loja city during the 2020 - 2021 school year. The methods used in this research were the scientific, the descriptive, the statistical and the analytical-synthetic. The Instruments used were tests and questionnaires to know the students' level in writing skills, observation sheets, and the field notes to record the students' performance and attitude towards the application of the strategy. The results indicated that students enhanced satisfactorily their writing skills in the use of vocabulary, word sentence order, coherence and punctuation. In conclusion, the mechanics strategy was effective to improve satisfactorily students' writing skills. It increased learners' interest in writing correctly by applying the rules of punctuation, coherence, a larger lexicon and above all a proper word sentence order, in each writing task